Mengenali Kebijakan Kampus Mengajar - Sabana, Siti Azahra Walidatus; Pradika, Prana Wahyu Tri Adji (YASIN, 2022)
Educational institutions are the foundation of human values by accepting various kinds of things that students have. Both gender diversity, traditions, persons with disabilities, special, and social diversity. Acceptance The diversity of students is a challenge for educational institutions to organize inclusive madrasas. and obstacles in the form of availability of funds, competent teachers, seriousness of the institution, and lack of network relations. An ideal educational institution capable of providing optimal services based on the belief that all students are equal and have the right to receive the same education and receive education according to their level. So madrasas that have a great determination to become inclusive institutions are institutions that uphold human aspects in the world of education.